Impact of accounting system on individual: a case study of YCS Management & Consulting Service, Johor Bahru - Abu Seman, Noor Aslinda; Fernandez, Dahlia (Penerbit UTHM, 2020)
The changing in information technology has occured approximately at each stage of human life but being thought in a different way or opinion at every stage (Peter et al., 2018). The nature of small or medium-sized enterprises (SME) are also affected by the quick changes in technology over the passage of time, as well as growing demand from customers, had forced company to run business’s practice at both the technical level and strategic level of the organization (Dameri, Garilli, & Ricciardi, 2013; Shagari et al., 2017). Peter et al. (2018) also claimed that the utilization of computer technology has caused a great world-wide impact in all sectors of life and has made a massive transformation principally in the way of doing business both within and across countries. ..